Posisi Madrasah dalam Sistem Pendidikan Nasional di Era Otonomi Daerah - M. Daud Yahya (UIN Antasari Banjarmasin, 2017)
Madrasah is an Islamic educational institutions that have a long history, and finally recognized part of the National Education System . Madrasas are already managed by Depag / Kemenag with the religious sector is a problem when faced with the UU regions autonomy which necessitates the education sector be transferred to the government. At the end of the progress the school is not located in the under Depag and Kemenag but on the creativity the schools own.